2001
DOI: 10.1136/heart.85.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum concentrations of advanced glycation end products: a marker of coronary artery disease activity in type 2 diabetic patients

Abstract: Objective-To assess whether the concentrations of serum advanced glycation end products (AGE) in diabetic patients with obstructive coronary artery disease diVer from those in type 2 diabetic patients without obstructive coronary artery disease. Design-Serum AGE concentrations were measured in type 2 diabetic patients and in non-diabetic patients, both with and without obstructive coronary artery disease, and the relation between these values and coronary disease severity was evaluated. Results-Mean (SD) serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 18 publications
4
71
2
Order By: Relevance
“…Compared with the use of samples from skin biopsies for measurement of AGEs, serum samples are simple, and with standardisation they could become a useful clinical tool. Previous cross-sectional studies have demonstrated increased serum AGE levels in patients with type 2 diabetes and CVD [18,29]. Our study shows that high serum AGE levels predict total, CVD and CHD mortality in type 2 diabetic patients during long-term follow-up.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Compared with the use of samples from skin biopsies for measurement of AGEs, serum samples are simple, and with standardisation they could become a useful clinical tool. Previous cross-sectional studies have demonstrated increased serum AGE levels in patients with type 2 diabetes and CVD [18,29]. Our study shows that high serum AGE levels predict total, CVD and CHD mortality in type 2 diabetic patients during long-term follow-up.…”
Section: Discussionsupporting
confidence: 49%
“…Experimental studies in animals and in humans have shown that treatments that break the crosslinks result in greater vascular compliance [16,17]. In a cross-sectional study, elevated levels of circulating AGEs correlated with the extent of coronary artery occlusion in type 2 diabetic patients [18]. We recently reported that high serum levels of AGEs predict mortality from CHD in nondiabetic women, but not in non-diabetic men [19].…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes mellitus, AGE accumulation in skin collagen is correlated both with the duration and severity of hyperglycaemia, and with the presence of long-term complications [6,7,8,12,13,14,15]. In a DCCT substudy, skin AGE levels explained 19 to 36% of the variance in the incidence of long-term diabetic complications in intensively treated patients, and 14 to 51% in conventionally treated patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, cTnT release from injured myocardium may have a longer circulating half-life compared with cTnI because of advanced glycation end products known to accumulate in diabetic patients with renal disease. 28 However, future studies need to evaluate this concept. Third, two small studies have suggested that cTnI decreases after dialysis, either directly attributable to removal by dialysis or indirectly by degradation of the labile cTnI molecule.…”
Section: Apple Et Al Prognostic Value Of Troponin In Renal Disease 2943mentioning
confidence: 99%